A new method for real time computation of power quality indices based on instantaneous space phasors - Milanese, Dalgerti L. [UNESP]; Ciric, Rade M. (My University, 2004)
One of the important issues about using renewable energy is the integration of dispersed generation in the distribution networks. Previous experience has shown that the integration of dispersed generation can improve voltage profile in the network, decrease loss etc. but can create safety and technical problems as well, This work report the application of the instantaneous space phasors and the instantaneous complex power in observing performances of the distribution networks with dispersed generators in steady state. New IEEE apparent power definition, the so called Buccholz-Goodhue apparent power, as well as new proposed power quality (oscillation) index in the three-phase distribution systems with unbalanced loads and dispersed generators, are applied. Results obtained from several case studies using IEEE 34 nodes test network are presented and discussed.
Keywords: Dispersed generators; Instantaneous space phasors; Power definitions; Unbalance; Computational complexity; Electric power distribution; Oscillations; Problem solving; Renewable energy resources; Electric generators